Bioethanol production from Palmyrah (Borassus flabellifer) wastes using yeast - Christy, E.J.S.B.A.; Mahilrajan, S.; Chandrasena, G.; Kapilan, R. (Sci.Foundation Sri Lanka, 2022)
This study describes bioethanol production from palmyrah (Borassus flabellifer L.) waste using yeast and optimization of fermentation conditions to increase the yield. When subjected to different pre-treatment conditions with various alkaline and acidic solutions, significantly higher reducing sugar contents were obtained from palmyrah coir dust with H2SO4 and HNO3 pre-treatments. H2SO4 pre-treatment at 3%, 5% and 7% concentrations for 15, 30, and 45 minutes respectively were given to the coir dust, and a significantly higher quantity of sugar was produced with 3% H2SO4 after 45 minutes of reaction. Among the acids and bases used for the pre-treatment, H2SO4 is the best hydrolysing agent for coir dust. When fermentation was done with the coir dust hydrolysed solution under optimized conditions [30 °C and pH 5.0 with baker’s yeast (6 × 106 cells mL-1) and incubated in peptone, yeast extract and nutrient (PYN) medium at 30 °C for 7 days] , a significantly higher amount of alcohol was produced on the 4th day than the respective non-optimized conditions. Similarly, molasses and fruit pulp of palmyrah also produced significantly higher quantities of ethanol individually under similar optimized conditions used for coir dust on the 6th and 4th day of fermentation respectively, than the respective non-optimized conditions. The efficiency of alcohol fermentation by yeast with palmyrah coir dust acid hydrolysate was 19%. Therefore, coir dust could also be used as a long-term substrate for bioethanol production, considering the excess availability of this underutilized waste material.
Keywords: Bioethanol; Coir dust; Fermentation; Molasses; Palmyrah; Pre-treatment